ANALISIS FINANSIAL USAHA BUDIDAYA RUMPUT LAUT (Gracilaria sp) DI TANJUNG SEMBILANG KECAMATAN SAMBOJA - Riki; Gusti Haqiqiansyah; Muhammad Syafril (Jurnal Pembangunan Perikanan dan Agribisnis, 2020)
The purpose of this research is to Analyze the financial feasibility of seaweed farming (Gracilaria sp) in Tanjung Sembilang, Samboja District and to know the driving factors and inhibiting factors of seaweed cultivation (Gracilaria sp) in Tanjung Sembilang, Samboja District.This research was conducted for 1 month in Muara Sembilang Village, Samboja District, the sampling method used the census method. Data analyzed using financial analysis.The results showed that the seaweed cultivation business (Gracilaria Sp) conducted by farmers in Tanjung Sembilang, Samboja District was financially feasible to be carried out within the next five years, with a NPV value of Rp. 159,050,728, IRR = 40%, Net B / C Ratio = 1.55, and Payback Period = 3.22 and the driving factor of seaweed farming (Gracilaria Sp) is the existence of penggawa as a source of capital and the existence of marketing channels in Muara Sembilang. The inhibiting factors of seaweed cultivation (Gracilaria Sp) are pests and diseases, limited business capital, weather, relatively cheap selling prices at the level of farmers, and the role of extension agents.